Co-pyrolysis characteristics and product distributions of municipal solid waste and corn stalk. Issue 5 (4th March 2018) - Jia, Jinwei; Liu, Lu; Yang, Fengsheng; Fu, Xiaoheng; Yang, Di; Hui, Helong; Fu, Xingmin; Shu, Xinqian
ABSTRACT: To investigate synergetic effects on pyrolysis of municipal solid waste and corn stalk, pyrolysis characteristics and product distributions of their mixtures were examined by thermal gravimetric and fixed-bed. Results indicated that co-pyrolysis process can be divided into four steps: losing water, main pyrolysis, carbonization and catalytic gasification of char. Under different blending ratio conditions, char and liquid yields were lower than the theoretical values calculated on pyrolysis of each individual sample, and consequently, gas yields were higher. Linear relationship can be applied to char and liquid products, however, hardly applied to gas yields.